A giant protocluster of galaxies at redshift 5.7. (December 2018) - Jiang, Linhua; Wu, Jin; Bian, Fuyan; Chiang, Yi-Kuan; Ho, Luis; Shen, Yue; Zheng, Zhen-Ya; Bailey, John; Blanc, Guillermo; Crane, Jeffrey; Fan, Xiaohui; Mateo, Mario; et al.
Abstract Galaxy clusters trace the largest structures of the Universe and provide ideal laboratories for studying galaxy evolution and cosmology1, 2 . Clusters with extended X-ray emission have been discovered at redshifts of up to z ≈ 2.5 (refs3–7 ). Meanwhile, there has been growing interest in hunting for protoclusters, the progenitors of clusters, at higher redshifts8–14 . It is, however, very challenging to find the largest protoclusters at early times, when they start to assemble. Here, we report a giant protocluster of galaxies at z ≈ 5.7, when the Universe was only one billion years old. This protocluster occupies a volume of about 353 cubic comoving megaparsecs. It is embedded in an even larger overdense region with at least 41 spectroscopically confirmed, luminous Lyα-emitting galaxies (Lyα emitters, or LAEs), including several previously reported LAEs9 . Its LAE density is 6.6 times the average density at z ≈ 5.7. It is the only one of its kind in an LAE survey in 4 deg2 on the sky. Such a large structure is also rarely seen in current cosmological simulations. This protocluster will collapse into a galaxy cluster with a mass of (3.6 ± 0.9) × 1015 solar masses, comparable to those of the most massive clusters or protoclusters known so far. A giant protocluster of galaxies at redshift z ≈ 5.7 is found within a large overdense region containing at least 41 spectroscopically confirmed Lyα-emitting galaxies. It will collapse into one of the most massive clusters known to date.